Knowledge and Prevention Behavior of Post-COVID-19 Vaccination - Ni Putu Ayu Wulan Noviyanti; Putu Ratna Suprima Dewi; Ni Putu Eka Febianingsih (Babali Nursing Research, 2022)
Introduction: Vaccination is one part of COVID-19 prevention to provide immunity against virus that is being targeted. People who have been vaccinated against COVID-19 should continue to carry out prevention behavior towards COVID-19. This study aims to determine the knowledge and prevention behavior towards COVID-19 in people who have received the COVID-19 vaccine.